The Effect of Moveable Fins on Trajectory and Aerodynamic Characteristics of Model Rockets - Nicholas Bawing Jampi; Mohd Fadhli Zulkafli (Progress in Aerospace and Aviation Technology, 2024)
The application of the fins on the rocket are necessary to achieve optimal flight performance. However, the appearance of gust wind can affect the stability of the rocket during flight. To minimize instability, the fins are designed to be adjustable by changing the fin cant angles. This study aims to investigate the effect of different cant angles on rocket’s trajectory and aerodynamic characteristics through computer simulation. The Open Rocket software is used to conduct the simulations. The range of cant angle in this study is from 0° to 15° and the Clipped Delta fin design is chosen for this study. The launch condition is all the same for all the model rockets and the launch site’s latitude and longitude was based on Parit Raja location. The trajectory characteristics were evaluated through simulations of altitude versus position east of launch, altitude versus position north of launch, and altitude versus lateral distance. Meanwhile, the aerodynamic characteristics were evaluated through simulations of stability margin and drag force over time. This study found that the maximum altitude for each model rocket is decreasing as the cant angle increases. Different fin’s cant angles slightly alter the trajectory characteristic of model rockets, but they do not significantly impact the overall stability and drag characteristics during critical phases of flight. Higher cant angles resulted in shorter horizontal and lateral distances from the launch site to the apogee, suggesting a more vertical trajectory.